Syncopation creates the sensation of groove in synthesized music examples - Sioros, George; Miron, Marius; Davies, Matthew; Gouyon, Fabien; Madison, Guy (Frontiers in Psychology, 2014)
In order to better understand the musical properties which elicit an increased sensation of wanting to move when listening to music – groove – we investigate the effect of adding syncopation to simple piano melodies, under the hypothesis that syncopation is correlated to groove. Across two experiments we examine listeners’ experience of groove to synthesized musical stimuli covering a range of syncopation levels and densities of musical events, according to formal rules implemented by a computer algorithm that shifts musical events from strong to weak metrical positions. Results indicate that moderate levels of syncopation lead to significantly higher groove ratings than melodies without any syncopation or with maximum possible syncopation. A comparison between the various trans-formations and the way they were rated shows that there is no simple relation between syncopation magnitude and groove.